Legal Analysis of The Position of Separated Creditors Regarding Guarantee Rights in Bankruptcy - La Ode Maskur; Wa Ode Novita Ayu Muthmainna (AIQU: Journal Multidiscipliner of Science, 2025)
This study aims to analyze the legal position and legal consequences for secured creditors (separatist creditors) holding security rights in bankruptcy proceedings. Separatist creditors are those who possess collateral rights such as mortgage, fiduciary transfer, hypothec, or pledge over the debtor's assets, theoretically entitling them to preferential repayment from the execution of those assets. However, in practice particularly within the framework of bankruptcy these rights often conflict with provisions stipulated in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (the Indonesian Bankruptcy Law). This research employs a normative juridical method using a statutory and conceptual approach, with qualitative analysis of primary, secondary, and tertiary legal materials. The findings reveal that although Article 55 of the Bankruptcy Law recognizes the right of separatist creditors to execute their collateral as if bankruptcy did not occur, Articles 56, 57, and 58 impose significant restrictions, such as execution moratoriums and intervention by the curator. As a result, secured creditors face legal uncertainty, diminished priority rights, and potential disputes with the curator. These legal inconsistencies reflect the lack of harmony between bankruptcy law and collateral law. Therefore, legal reform is needed to align the Bankruptcy Law with collateral regulations, the Civil Code, and other sectoral laws such as taxation and labor regulations. Such harmonization is crucial to ensure legal certainty and fairness for all parties involved in bankruptcy proceedings.